2021
DOI: 10.1002/ece3.8460
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drivers of spatial genetic variation of a ground‐dwelling bird species and its implications for conservation

Abstract: In modern wildlife ecology, spatial population genetic methods are becoming increasingly applied. Especially for animal species in fragmented landscapes, preservation of gene flow becomes a high priority target in order to restore genetic diversity and prevent local extinction. Within Central Europe, the Alps represent the core distribution area of the black grouse, Lyrurus tetrix. At its easternmost Alpine range, events of subpopulation extinction have already been documented in the past decades. Molecular da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 147 publications
(181 reference statements)
2
3
0
Order By: Relevance
“…This pattern agrees with the genetic structure observed in Spain, where some genetic clusters are not entirely isolated . Similar patterns have been identified for other bird species mainly because of their high dispersal capacities (Kleinhans & Willows-Munro, 2019;Koopman et al, 2007;Kunz et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This pattern agrees with the genetic structure observed in Spain, where some genetic clusters are not entirely isolated . Similar patterns have been identified for other bird species mainly because of their high dispersal capacities (Kleinhans & Willows-Munro, 2019;Koopman et al, 2007;Kunz et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…This pattern agrees with the genetic structure observed in Spain, where some genetic clusters are not entirely isolated (Méndez, Tella, & Godoy, 2011 ). Similar patterns have been identified for other bird species mainly because of their high dispersal capacities (Kleinhans & Willows‐Munro, 2019 ; Koopman et al., 2007 ; Kunz et al., 2022 ). To directly evaluate the landscape influence on the stepping‐stone connectivity, future studies should consider a sampling design that specifically accounts for the habitat features of patches potentially serving as stepping stones (Duforet‐Frebourg & Slatkin, 2016 ).…”
Section: Discussionsupporting
confidence: 77%
“…For example, Seaborn et al ( 2019 ) found that although individual‐based sampling was helpful for increasing sampling extent and density, it may lack power for model comparisons compared with population‐based sampling. Kunz et al ( 2022 ) also found differing support for IBD versus IBR among individuals compared to among subpopulations. In our case, given the lack of clear subpopulations or distinct sampling areas within our sample, an individual‐based approach was both necessary and justified.…”
Section: Discussionmentioning
confidence: 99%
“…The IBR framework can improve understanding of how a broad range of landscape features and characteristics simultaneously influence gene flow and movement, ultimately allowing researchers to predict both ecological and evolutionary consequences of landscape change. By investigating the roles of isolation by distance (IBD) and isolation by resistance (IBR) in determining genetic structure, we can gain a more complete understanding of the effects of spatial distance and habitat heterogeneity on species distribution, abundance, and movement (Kunz et al, 2022 ; McRae, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, dispersal ability could influence range limits and gene flow among populations, which may be associated with niche differentiation. In addition, previous studies showed that morphological adaptation to local ecology can also have resulted from phenotypic plasticity or from genetic differences among populations (Borokini et al, 2021 ; Ghalambor et al, 2007 ; Kunz et al, 2022 ; Price et al, 2003 ; Schmid & Guillaume, 2017 ). Although phenotypic plasticity has been documented in response to variations in multiple environmental variables (Chevin & Lande, 2015 ; Gratani, 2014 ; Lande, 2009 ; Wang et al, 2021 ), we found morphological distance was not correlated with environmental distance after controlling for geographic distance (Table 6 ).…”
Section: Discussionmentioning
confidence: 99%